Perspectives on Marine Electromagnetic Methods - Steven Constable (Perspectives of Earth and Space Scientists)
Abstract Marine electromagnetic methods form important tools for the study of offshore geology, particularly at plate boundaries such as mid‐ocean ridges, subduction zones, and the boundary between the lithosphere and asthenosphere, because electrical conductivity is strongly dependent on water content, partial melt, and temperature. Very early development of electromagnetic methods in the oceans was driven by military interest in marine communication and detection, and geological applications soon followed. Around the turn of the century, what was originally a niche discipline expanded dramatically when the hydrocarbon industry embraced magnetotelluric and controlled‐source electromagnetic methods as aids to deep‐water exploration, driving a significant improvement in instrumentation and interpretation software. This greatly enhanced the imaging capabilities of these methods, and led to an expansion of their academic use both in plate boundary studies and newer applications such as gas hydrate studies, offshore groundwater mapping, and others.